Research evolution on self-healing asphalt: A scientometric review for knowledge mapping - Khan Kaffayatullah; Ahmad Waqas; Amin Muhammad Nasir; Khan Suleman Ayub; Deifalla Ahmed Farouk; Younes Mohammad Yousef Mohammad (Reviews on Advanced Materials Science, 2023)
This study employed a novel approach by analyzing the self-healing asphalt literature based on scientometric analysis. The most difficult components of modern study are the mapping and analysis of knowledge, co-citations, and co-occurrences. Scopus was searched to find the necessary data for the analysis, which consisted of keywords, abstracts, citations, and bibliographic information. Throughout the data assessment process, the most prolific research locations, the most often referenced articles, and the most influential authors in the field of self-healing asphalt were analyzed, along with their correlations. The need for self-repairing asphalt was also emphasized, along with the main problems of using it. The keyword analysis showed that researchers have studied self-healing asphalt for crack repair in asphalt road pavements as a sustainable maintenance method. The literature study showed that heating and encapsulating rejuvenating chemicals are two techniques of self-healing asphalt. Encapsulation uses rejuvenating capsules, whereas the heating technique uses induction heating and microwave radiation. Researchers have also developed hybrid asphalt self-healing methods as enhanced self-healing for asphalt. Academics may benefit from the quantitative assessment of regions and researchers as well as the scientific description of these areas in order to form joint initiatives and spread new ideas and approaches.